Pattern and outcome of admissions in a neonatal high dependency unit of a medical college hospital in Khulna, Bangladesh - Ali, MB; Maruf, AA; Rashid, MM (Mediscope, 2018)
To determine the pattern and outcome of admitted patients in neonatal high dependency unit of a medical college hospital in Khulna, Bangladesh the patients in this study were included from January 2016 to December 2016. Data of all the neonatal admissions were recorded and analyzed for age, gender, weight at the time of admission, place of delivery, the reason for admission, duration of hospital stay and the final outcome of the patients. A total of 433 neonates were admitted during the year 2016. Among them, 262 (60.5%) were male and 171 (39.5%) female patients. Majority of the newborns, 255 (58.9%), were admitted within 24 hours of life. Most of the patients, 365 (84.3%), were born in hospitals/ private clinics and the others, 68 (15.7%), at home. Major causes of admissions were sepsis 115 (26.6%), neonatal jaundice 102 (23.6%), low birth weight (LBW) 61 (14.1%), birth asphyxia 48 (11.1%), preterm 27 (6.2%), meconium aspiration 22 (5.1%), respiratory distress syndrome (RDS) 19 (4.4%) and intrauterine growth retardation 18 (4.2%). Most of the patients, 215 (49.7%), were admitted for 2-5 days followed by 118 (27.3) patients for 6-10 days. Three hundred seventy (85.4%) babies were discharged after improvement, 18 (4.2%) babies referred to higher centers, 20 (4.6%) discharged against medical advice and 25 (5.8%) deceased. The deceased were most frequently with neonatal sepsis 9 (36.0%) followed by prematurity 6 (24.0%), birth asphyxia 3 (12.0%), RDS 2 (8.0%), meconium aspiration 3 (12.0%) and multiple congenital anomalies 2 (8.0%). Sepsis, neonatal jaundice, LBW, birth asphyxia were the main causes of neonatal admissions. Common causes of neonatal mortality were sepsis, prematurity and birth asphyxia. The majority of morbidities and subsequently the mortalities can be prevented by improving antenatal care, maternal health, timely intervention, referring at an appropriate time to tertiary care centers. Mediscope Vol. 5, No. 2: Jul 2018, Page 1-7